Schwa au niveau avancé du français langue seconde - Thomas, Alain (Canadian Journal of Applied Linguistics, 2010)
This research is part of a large-scale survey on the oral performance of advanced French-as-a-second-language (FL2) students, as represented by recorded speech, both in spontaneous and reading styles. Although /schwa/ rarely leads to semantic confusions, its analysis in word-median or monosyllabic contexts shows interesting phonostylistic variations. After global results have been compared to previous research in this area, the students' progress in one year will be analyzed by contrasting pre-test and post-test results. Eventual differences between the experimental group (3rd year of university spent in France) and the control group (3rd year in Ontario) will be examined. Results point in the same direction as other optional phonetic variables previously studied: FL2 students- especially members of the control group- tend to be much more conservative than native French speakers in their use of spoken French.